Transforming literacy curriculum genres : working with teacher researchers in urban classrooms - Pappas, Christine; Zecker, Liliana Barro (L. Erlbaum Associates, 2001)
This study was based on inquiries on various literacy topics, conducted in urban schools as part of an action research project. Attempts to adapt teaching practice to meet the needs of pupils from diverse ethnic and linguistic backgrounds resulted in developing more collaborative styles of teaching.